Neurocysticercosis : from diagnosis to treatment - Chavez, Mark A. (New York : Nova Science Publishers, 2021)
"Neurocysticercosis, a preventable parasitic infection of the central nervous system caused by tapeworm, is a serious, potentially fatal disease that can cause neurologic syndromes such as epileptic seizures. Chapter One of this monograph describes the existing treatment options for neurocysticercosis, along with possible therapeutic alternatives under different drug development phases. Chapter Two explains the difficulties associated with correctly diagnosing neurocysticercosis, resulting from its varied clinical presentation, and mentions current guidelines of diagnostic criteria for neurocysticercosis. Chapter Three describes the various merits and demerits of techniques for detecting the parasites associated with neurocysticercosis, which include radioimaging, genotyping of cysts, and antibody, antigen, and nucleic acid detection in body fluids"--
Excretory-Secretory Antigens -- Purified Antigenic Fractions -- Recombinant Antigens -- Antigen Detection -- Urine and Saliva Samples -- Nucleic Acid Detection -- Polymerase Chain Reaction (PCR) -- Loop-Mediated Isothermal Amplification (LAMP) -- Genotype Variation in the Parasite -- Proteomics -- Cell Mediated Techniques -- Clinical Considerations -- Presentation vs. Diagnosis -- Single vs. Multiple Lesions -- Childhood NCC -- Post-Treatment Follow-Up -- Conclusion -- References -- Index -- Blank Page.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Central nervous system; Cysticercosis; Central Nervous System; Cysticercosis; Système nerveux central; Cysticercose; Central nervous system; Cysticercosis